Are veterinary entrepreneurs successful? An X-ray of Influential factors - Otero, Jorge (2024)
This qualitative research study describes and determines the level of success of veterinary enterprises in the district of El Agustino, Lima, Peru, in 2022. Two surveys were conducted, one for veterinary business owners and another for their clients. The first survey considered only businesses that employed veterinarians, excluding those devoted to pet grooming or selling accessories and food, commonly referred to as “pet shops.” The study’s independent variables include entrepreneurial attitude, which involves five factors (need for achievement, innovation, perceived internal control, self-esteem, and risk-taking), and production factors variable, which are work and capital. The dependent variable is business success, encompassing customer satisfaction and monthly business profits. Methodologically, six stages were employed to determine the success level of each veterinary business. The first stage assessed the sub-indicators of each indicator; the second one assessed the indicators of each factor in terms of adequacy categories; the third one analyzed each factor of the variables in success categories; the fourth one assessed each variable in success categories; the fifth one determined the effect of each variable in success categories; and the sixth one established the success levels of veterinary ventures based on the relationship between the independent and dependent variables. The results revealed that 44.44% of the veterinary practices studied are moderately successful according to the parameters used, while 55.56% are minimally successful. As for veterinary clinics, 50.00% were classified as minimally successful, and the other 50.00% as moderately successful. None of the ventures achieved a fully successful level.